Optimization of Multilocus Sequence Analysis for Identification of Species in the Genus Vibrio - Gabriel, Michael W. (American Society for Microbiology, 2014)
Multilocus sequence analysis (MLSA) is an important method for identification of taxa that are not well differentiated by 16S rRNA gene sequences alone. In this procedure, concatenated sequences of selected genes are constructed and then analyzed. The effects that the number and the order of genes used in MLSA have on reconstruction of phylogenetic relationships were examined. The recA, rpoA, gapA, 16S rRNA gene, gyrB, and ftsZ sequences from 56 species of the genus Vibrio were used to construct molecular phylogenies, and these were evaluated individually and using various gene combinations. Phylogenies from two-gene sequences employing recA and rpoA in both possible gene orders were different. The addition of the gapA gene sequence, producing all six possible concatenated sequences, reduced the differences in phylogenies to degrees of statistical (bootstrap) support for some nodes. The overall statistical support for the phylogenetic tree, assayed on the basis of a reliability score (calculated from the number of nodes having bootstrap values of ≥80 divided by the total number of nodes) increased with increasing numbers of genes used, up to a maximum of four. No further improvement was observed from addition of the fifth gene sequence (ftsZ), and addition of the sixth gene (gyrB) resulted in lower proportions of strongly supported nodes. Reductions in the numbers of strongly supported nodes were also observed when maximum parsimony was employed for tree construction. Use of a small number of gene sequences in MLSA resulted in accurate identification of Vibrio species.